Uncovering the gaps: a grounded theory approach to conceptualizing inadequate child family caregiving in China - Jia-Yuan, Zhang; Jinwei, Yang; Yuqiu, Zhou (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the manifestations of inadequate family caregiving for children in China and aims to construct a conceptual framework that captures the multifaceted nature of this phenomenon within a rapidly changing social context.MethodsBased on constructivist grounded theory, in-depth interviews were conducted with 28 children and their primary family caregivers across diverse socioeconomic backgrounds, selected through purposive and theoretical sampling. Through open, axial, and selective coding, this study identified and refined the core attributes, antecedents, and outcomes of inadequate family caregiving, ultimately developing a conceptual framework.ResultsThrough the coding process, four core dimensions of caregiving insufficiencies were identified: daily living care, emotional and psychological support, safety supervision, and educational guidance. These gaps in caregiving were found to stem from a combination of internal family factors, such as unstable caregiving structures, limited parenting knowledge, low motivation, and insufficient caregiving skills, as well as external challenges, including limited family and community support and sociocultural pressures. The study found that these caregiving gaps were linked to strained parent–child relationships, delays in social and emotional development, behavioral issues, and potential risks to children’s physical health.ConclusionInadequate family caregiving emerges from a mix of internal and external constraints that limit caregiving capacities and resource access, resulting in multidimensional caregiving deficiencies that impact children’s physical and mental health. Addressing this issue necessitates enhancing family caregiving capacities, strengthening social support networks.